Material sensitivity of patient-specific finite element models in the brace treatment of scoliosis - Wei, Wenqing; Zhang, Tianyuan; Yang, Junlin; Qian, Yu; Dong, Yating (Frontiers in Bioengineering and Biotechnology, 2023)
Objectives. To study the mechanical sensitivity of different intervertebral disc and bone material parameters and ligaments under different force configurations and magnitudes in the scoliosis model. Methods. The finite element model of a 21-year-old female is built using computed tomography. Local range of motion testing and global bending simulations are performed for the model verification. Subsequently, five force configurations are applied to a patient-specific model with different mechanical parameters. The virtual X-ray technique measured Cobb angle, thoracic lordosis, and lumbar kyphosis. Results. The difference in peak displacement is 9.28 mm, 19.99 mm, 27.06 mm, 43.99 mm, and 50.1 mm under five force configurations. The average difference in thoracic Cobb angle correction is 14.53%, and the average difference in lumbar Cobb angle correction is 11.8%. The maximum difference in kyphosis and lordosis is 4.4° and 5.8°, respectively. The displacement distribution of models with or without ligaments is similar, with a peak displacement difference of 1.3 mm. The peak stress occurred at the junction of the cortical bone and ribs. Conclusion. Patient-specific material is the key to increasing accuracy in the personalized finite element model. This study provides a scientific basis for using brace treatment for scoliosis.